The Layered Anatomy of the Nose: An Ultrasound-Based Investigation. (7th August 2021) - Alfertshofer, Michael G; Frank, Konstantin; Ehrl, Denis; Freytag, David L; Moellhoff, Nicholas; Gotkin, Robert H; Mardini, Samir; Beleznay, Katie; Swift, Arthur; Cotofana, Sebastian
Abstract: Background: An increasing number of soft tissue filler procedures in the nasal region has been reported. Concomitant with demand, the number of complications has risen due to the difficulty in administering filler in a region where soft tissue layering is complex. Objectives: The authors sought to describe the layered soft tissue arrangement of the nose as it relates to the underlying arterial vasculature and to define safer zones for nasal filler enhancement. Methods: A total of 60 (28 males and 32 females) study participants were investigated with respect to their layered anatomy in the midline of the nose utilizing ultrasound imaging. The presence and extent of the layered arrangement was examined as well as the depth of the arterial vasculature. Results: In the mid-nasal dorsum, a 5-layer arrangement was observed in 100% (n = 60) of all investigated cases, whereas it was found to be absent in the nasal radix and tip. The 5-layer arrangement showed an average extent of 26.7% to 67.5% in relation to nasal length. The nasal arteries coursed superficially in 91.7% of all cases in the nasal radix, in 80% in the mid-nasal dorsum, and in 98.3% in the nasal tip. Conclusions: Soft tissue filler administration in the nose carries the highest risk for irreversible vision loss compared with any other facial region. The safety of soft tissue filler rhinoplasty procedures is enhanced by knowledge of the layered anatomy of the nose, the location and depth of the major nasal vasculature, and employment of maneuvers to decrease the risk of blindness.